Adventitia‐derived extracellular matrix hydrogel enhances contractility of human vasa vasorum‐derived pericytes via α2β1 integrin and TGFβ receptor. Issue 12 (30th June 2022) - Wintruba, Kaitlyn L.; Hill, Jennifer C.; Richards, Tara D.; Lee, Yoojin C.; Kaczorowski, David J.; Sultan, Ibrahim; Badylak, Stephen F.; Billaud, Marie; Gleason, Thomas G.; Phillippi, Julie A.
Abstract: Pericytes are essential components of small blood vessels and are found in human aortic vasa vasorum. Prior work uncovered lower vasa vasorum density and decreased levels of pro‐angiogenic growth factors in adventitial specimens of human ascending thoracic aortic aneurysm. We hypothesized that adventitial extracellular matrix (ECM) from normal aorta promotes pericyte function by increasing pericyte contractile function through mechanisms deficient in ECM derived from aneurysmal aortic adventitia. ECM biomaterials were prepared as lyophilized particulates from decellularized adventitial specimens of human and porcine aorta. Immortalized human aortic adventitia‐derived pericytes were cultured within Type I collagen gels in the presence or absence of human or porcine adventitial ECMs. Cell contractility index was quantified by measuring the gel area immediately following gelation and after 48 h of culture. Normal human and porcine adventitial ECM increased contractility of pericytes when compared with pericytes cultured in absence of adventitial ECM. In contrast, aneurysm‐derived human adventitial ECM failed to promote pericyte contractility. Pharmacological inhibition of TGFβR1 and antibody blockade of α2 β1 integrin independently decreased porcine adventitial ECM‐induced pericyte contractility. By increasing pericyte contractility, adventitial ECM may improve microvascular function and thus represents a candidate biomaterial for less invasive and preventative treatment of human ascending aortic disease.